2017
DOI: 10.1021/acs.analchem.7b02508
|View full text |Cite
|
Sign up to set email alerts
|

Selective Amperometric Recording of Endogenous Ascorbate Secretion from a Single Rat Adrenal Chromaffin Cell with Pretreated Carbon Fiber Microelectrodes

Abstract: Quantitative description of ascorbate secretion at a single-cell level is of great importance in physiological studies; however, most studies on the ascorbate secretion have so far been performed through analyzing cell extracts with high performance liquid chromatography, which lacks time resolution and analytical performance on a single-cell level. This study demonstrates a single-cell amperometry with carbon fiber microelectrodes (CFEs) to selectively monitor amperometric vesicular secretion of endogenous as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…For example, ascorbate can be directly transported into neurons through the sodium‐dependent vitamin C transporter‐2, or the oxidized form of ascorbate can be transported into astrocytes and subsequently reduced to ascorbate by glucose transporters . We and others have also demonstrated a vesicular‐mediated or volume‐sensitive organic anion channel (VSOAC) mediated release of ascorbate . Among those findings, the glutamate‐ascorbate hetero‐exchange mechanism is the most invoked, in which ascorbate is released to extracellular spaces to promote glutamate uptake into cells to alleviate excitotoxicity in some pathological processes, including SD.…”
Section: Figurementioning
confidence: 90%
“…For example, ascorbate can be directly transported into neurons through the sodium‐dependent vitamin C transporter‐2, or the oxidized form of ascorbate can be transported into astrocytes and subsequently reduced to ascorbate by glucose transporters . We and others have also demonstrated a vesicular‐mediated or volume‐sensitive organic anion channel (VSOAC) mediated release of ascorbate . Among those findings, the glutamate‐ascorbate hetero‐exchange mechanism is the most invoked, in which ascorbate is released to extracellular spaces to promote glutamate uptake into cells to alleviate excitotoxicity in some pathological processes, including SD.…”
Section: Figurementioning
confidence: 90%
“…For example, we found that VC can be released in the form of nanoscale vesicles, the main pathway that is commonly preserved in the regulated secretion of neurotransmitters by neurons (Figure 15(b)). [175] Moreover, we observed for the first time that the propagative nature of VC release following the spreading diffusion process, highlighting its importance as a neuromodulator in mediating neurotransmission (Figure 15(a)). [176] Furthermore, through our longterm collaboration with Peking University Third Hospital, which specializes in designing, establishing and evaluation of clinical relevant disease models, we demonstrated that VC plays more important roles other than just as free radical scavengers for neuro-protection in the events of tinnitus , olfactory dysfunction and Vertigo [177].…”
Section: Neurobiology Studies Enabled By New In Vivo Analytical Methodsmentioning
confidence: 77%
“… 69 , 70 Second, material released from vesicles or droplets provides a natural ex vivo mimic of extracellular release processes, e.g., neurotransmitters released from neurons. 71 , 72 Early work addressing single nanoparticle collisions was conducted on ultramicroeletrodes by Bard et al 73 and others. 74 76 Since these early reports, it has become possible to sequester a few nanoparticles, or even one.…”
Section: Nanopore Electrode Capabilitiesmentioning
confidence: 99%